THE INSTITUTIONAL ROLE IN FACILITATING THE ADVANCEMENT OF EQUATOR PARK TOURISM WITHIN THE VILLAGE OF JERUJU BESAR - wulan dari, Selvi Seri; Imtinan, Aisyah Hilya; Rahmadanti, Dhita; Listyaningrum , Indah; Kurniawan, Edi; Lestari, Rosi (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2023)
The research aims to determine the role of local institutions in the development of Equator Park tourism in Jeruju Besar Village, Sungai Kakap District. The descriptive method is a useful option for describing, depicting and analyzing objects, conditions, and responses to an event that occurred in the Equator Park development. The results of this research are that Equator Park was built with the involvement of local institutions, namely POKDARWIS through role indicators at the preparatory stage. The imitating stage, Equator Park is inspired by Telok Standing Ecotourism which is on the Kupah River, this ecotourism also takes advantage of nature's preservation. Human Resources there use tickets for operational funds so that the rides there can be properly maintained. The last stage is the stage of accepting collective norms, with this stage the level of concern for villagers also increases